Insulin analogues use in pregnancy among women with pregestational diabetes mellitus and risk of congenital anomaly: a retrospective population-based cohort study. Issue 2 (24th February 2018) - Wang, Hao; Wender-Ozegowska, Ewa; Garne, Ester; Morgan, Margery; Loane, Maria; Morris, Joan K; Bakker, Marian K; Gatt, Miriam; de Walle, Hermien; Jordan, Susan; Materna-Kiryluk, Anna; Nelen, Vera; et al.
Abstract : Objectives: To evaluate the risk of major congenital anomaly associated with first-trimester exposure to insulin analogues compared with human insulin in offspring of women with pregestational diabetes. Design and setting: A population-based cohort of women with pregestational diabetes (n=1661) who delivered between 1996 and 2012 was established retrospectively from seven European regions covered bythe European Surveillance of Congenital Anomalies (EUROCAT) congenital anomaly registries. Primary outcome measures: The risk of non-chromosomal major congenital anomaly in live births, fetal deaths and terminations for a fetal anomaly exposed to insulin analogues in the first trimester of pregnancy was compared with the risk in those exposed to human insulin only. Results: During the first trimester, 870 fetuses (52.4%) were exposed to human insulin only, 397 fetuses (23.9%) to insulin analogues only and 394 fetuses (23.7%) to both human insulin and insulin analogues. The risk of major congenital anomaly in fetuses exposed to insulin analogues only was lower than those exposed to human insulin only; the relative risk adjusted for glycaemic control and region was 0.56 (95% CI 0.29 to 1.06). The significantly lower risk related to exposure of insulin analogues only was observed in congenital heart defects: adjusted relative risk 0.14 (95% CI 0.03 to 0.62). Conclusions: In this retrospective population-based cohort study across Europe, first-trimester exposure to insulin analogues did not increase the risk of major congenital anomaly compared with exposure to human insulin. A possible lower risk of congenital heart defects among fetuses exposed to insulin analogues only deserves further investigation.